Attitudinal Trends in CLIL Assessment: a pilot study - Jesús García Laborda; Elena Alcalde Peñalver (Tejuelo: Didáctica de la Lengua y la Literatura)
The aim of this paper is to present a pilot study based on a questionnaire distributed to prospective teachers of CLIL and non-CLIL courses with familiarity on that type of teaching due to their own studies either through graduate or undergraduate courses. The paper opens with an introduction to the topic and continues with a review of relevant research studies in the field of CLIL assessment. Next, the method of our study is presented with information about the instrument, participants and academic context. After that, the results of the study are analysed and illustrated with examples from the data. Finally, different interpretations of the study will be discussed as a way of conclusion. The preliminary results of this pilot study will show the most significant issues involved in CLIL assessment according to these prospective teachers’ expectations of what teaching following this methodology could be like.